1993
DOI: 10.1007/bf02372549
|View full text |Cite
|
Sign up to set email alerts
|

Biology ofAnastatus biproruli (Hym.: Eupelmidae) a parasitoid ofBiprorulus bibax (Hem.: Pentatomidae)

Abstract: The effect of temperature on the rate of development of Anastatus biproruli (Girault) was determined by rearing individuals on eggs of Biprorulus bibaxBreddin under a range of constant temperatures (17.5-40.0 *C). Rate of development changed in a linear fashion from 17.5-35.0 *C and the lower developmental threshold was estimated to be 12.8 ~ An estimated 331.8 degree days were required for development. Survival of developing parasitoids was optimal (72-90 %) between 25-35 ~ Longevity of virgin adults ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…in Australia. In a previous study James (1993) found that development rates of A. biproruli increased linearly between 17.5 and 35°C and in this study a similar relationship between development rate and rearing temperature was established for Anastatus sp. (Fig.…”
Section: A C C E P T E Dsupporting
confidence: 84%
See 1 more Smart Citation
“…in Australia. In a previous study James (1993) found that development rates of A. biproruli increased linearly between 17.5 and 35°C and in this study a similar relationship between development rate and rearing temperature was established for Anastatus sp. (Fig.…”
Section: A C C E P T E Dsupporting
confidence: 84%
“…5 nitida in Australia, although a previous study investigated the temperature relationships between Anastatus biproruli and its host, Biprorulus bibax (Hemiptera: Pentatomidae) (James 1993 Cockerell (Lepidoptera: Saturnidae) (Mendel et al 1987). Anastatus semiflavidus did not oviposit at temperatures ≤ 15°C, but the intrinsic rate of increase increased with increasing temperature between 20 and 35°C (Mendel et al 1987 semiflavidus parasitism rates are likely to be higher earlier in this period and may be significantly depressed in years experiencing cold autumn temperatures (Mendel et al 1987).…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…Recent biological and ecological studies on B. bibax (James, 1988(James, , 1989(James, , 1990a(James, , 1990b(James, , 1990c(James, , 1990d(James, , 1991(James, , 1992a(James, , 1992b(James, , 1993a(James, , 1993b(James, , 1993cJames & Warren, 1989, 1991James et al, 1990;Oliver et al, 1992) have provided information on population biology, physiology, development, host preferences, pheromones and natural enemies. Pertinent data from these studies were progressively utilized during 1987-92 to develop suppression tactics for B. bibax compatible with integrated pest management in citrus of inland southern Australia.…”
Section: Introductionmentioning
confidence: 99%
“…development rates declined at both 17.5°C and 30°C, the two extreme study temperatures. In contrast, James (1993) found that development rates of A. biproruli increased linearly between 17.5 and 35°C. The lower developmental threshold temperature for Anastatus sp.…”
Section: Development and Survival Of Anastatus Sp At Constant Tempermentioning
confidence: 43%
“…attacking A. nitida in Australia, although a previous study investigated the temperature relationships between Anastatus biproruli and its host, Biprorulus bibax (Hemiptera: Pentatomidae) (James 1993). Understanding the effects of temperature on the developmental biology of Anastatus sp.…”
Section: Introductionmentioning
confidence: 99%